Curious case of aqueous warfarin: structural isomers or distinct excited states? - Sakpal, Sushil S.; Ghosh, Deborin; Manae, Meghna A.; Hazra, Anirban; Bagchi, Sayan (Journal of Physical Chemistry B, 2021)
Warfarin is a potent anti-coagulant drug and is on the World Health Organization's List of Essential Medicines. Additionally, it displays fluorescence enhancement upon binding to human serum albumin, making warfarin a prototype fluorescent probe in biology. Despite its biological significance, the current structural assignment of warfarin in aqueous solution is based on indirect evidence in organic solvents. Warfarin is known to exist in different isomeric forms-open-chain, hemiketal, and anionic forms-based on the solvent and pH. Moreover, warfarin displays a dual absorption feature in several solvents, which has been employed to study the ring-chain isomerism between its open-chain and hemiketal isomers. In this study, our pH-dependent experiments on warfarin and structurally constrained warfarin derivatives in aqueous solution demonstrate that the structural assignment of warfarin solely on the basis of its absorption spectrum is erroneous. Using a combination of steady-state and time-resolved spectroscopic experiments, along with quantum chemical calculations, we assign the observed dual absorption to two distinct pi ->pi* transitions in the 4-hydroxycoumarin moiety of warfarin. Furthermore, we unambiguously identify the isomeric form of warfarin that binds to human serum albumin in aqueous buffer.

Water-controlled keto-enol tautomerization of a prebiotic nucleobase - Datar, Avdhoot; Paithankar, Harshad; Deb, Pranab; Chugh, Jeetender; Bagchi, Sayan; Mukherjee, Arnab; Hazra, Anirban (Journal of Physical Chemistry B, 2022)
Barbituric acid is believed to be a proto-RNA nucleobase that was used for biological information transfer on prebiotic earth before DNA and RNA in their present forms evolved. Nucleobases have various tautomeric forms and the relative stability of these forms is critical to their biological function. It has been shown that barbituric acid has a tri-keto form in the gas phase and an enol form in the solid state. However, its dominant tautomeric form in aqueous medium that is most relevant for biology has been investigated only to a limited extent and the findings are inconclusive. We have used multiple approaches, namely, molecular dynamics, quantum chemistry, NMR, and IR spectroscopy to determine the most stable tautomer of barbituric acid in solution. We find a delicate balance in the stability of the two tautomers, tri-keto and enol, which is tipped toward the enol as the extent of solvation by water increases.